Penetapan Kadar Kafein Pada Teh Kering Kemasan Produksi Industri Teh di Pekalongan - Rina Widhyani; Khusna Santika Rahmasari; Wirasti; Rini Kristiyanti; Slamet (Universitas Muhammadiyah Klaten, 2021)
Caffeine is one of the main alkaloid compounds in tea. The maximum limit of caffeine compounds in beverage food products based on SNI 01-7152-2006 is 50 mg / serving. Pekalongan has a packaged dry tea industry with a variety of brands, so caffeine content testing is required. This study aims to determine the differences in caffeine content in packaged dry tea produced by the tea industry in Pekalongan which is analyzed and to determine the caffeine content of all brands of tea samples that meet the maximum caffeine content requirements. The method used is the reverse phase High Performance Liquid Chromatography (HPLC) method with octadecyl silica C18 as stationary phase, methanol for HPLC mobile phase with a flow rate of 1 mL / minute and a wavelength of 274 nm. The results showed that there were differences in caffeine content in packaged dry tea produced by the tea industry in Pekalongan. The level of caffeine is 1.753 mg / g (T1), 4,870 mg / g (T2), 5,157 mg / g (T3), 2,394 mg / g (T4), 3,601 mg / g (T5), 3,275 mg / g (T6), 3,900 mg / g (T7), 3,725 mg / g (T8), 7,048 mg / g (T9) and 5,348 mg / g (T10). The ten brands of tea samples in a dose of 5 grams per serving have a caffeine content that meets the maximum limit requirements according to SNI 01-7152-2006, namely 50mg / serving with the highest caffeine content in sample T9. The ten brands of tea samples are safe for consumption